Uncle Sam's policemen: the pursuit of fugitives across borders - Unterman, Katherine (Harvard University Press, 2015)
Introduction: crimes of mobility -- The embezzlement epidemic -- Detectives without borders -- An empire of justice -- Extradition havens -- Asylum no more -- Camouflaged extradition -- From the Pinkertons to the FBI -- Epilogue: how rendition became extraordinary